ChemInform Abstract: Concepts in Theoretical Heterogeneous Ultrananocatalysis. Issue 36 (9th September 2014) - Negreiros, Fabio R.; Barcaro, Giovanni; Sementa, Luca; Fortunelli, Alessandro
Abstract Review: 76 refs.